Epizodysta naukowy – o pracy nauczyciela akademickiego. Między dydaktyką a nauką - Barańska, Magdalena; Nowak-Kluczyński , Konrad (Studia Edukacyjne, 2019)
Work at the university is a special type of professional activity. Being an academic teacher is a veryi nteresting, responsible and complex profession, but there is room for tasks, duties and roles between didactics and science which is not included in any definition. In the sheer volume of teaching, administrative and logistical duties, research is coming to the fore.